Marine nematodes of Canada. II. Marine nematodes from the Minas Basin - Scots Bay area of the Bay of Fundy, Nova Scotia - Hopper, B. E. (Can. J. Zool., 1969)
Locality: Scots Bay, Nova Scotia; Cabinet:
Locality: Scots Bay, Nova Scotia; Cabinet:; NeMys doc_id: 4564